Rapid detection of Ornithobacterium rhinotracheale infection by a latex agglutination test in turkeys - Sedigheh Yousefinejad; Mohammad Khosravi; Darioush Gharibi; Mansour Mayahi; Masoud Reza Seyfi Abad Shapouri (Poultry Science)
Ornithobacterium rhinotracheale (ORT) is a gram-negative pathogen recognized as one of the causative agents of respiratory diseases in chickens and turkeys. This study aimed to design and evaluate the diagnostic validity of the latex agglutination test for ORT detection. A Western blot test was conducted to assess the various serotypes present in the bacterial isolates, as well as the immunogenicity of their lipopolysaccharide. Following the design and optimization of the ELISA and latex agglutination tests using prepared mixed cell membrane antigens from the different isolates, a serological evaluation of the infection was performed on a total of 244 turkey serum samples, both with and without respiratory symptoms.The protein profiles of the isolated ORT samples revealed equal expression of proteins with molecular weights of 75 kDa and 100 kDa. The collected sera exhibited common antibodies that reacted with antigens weighing 48 kDa, 75 kDa and 100 kDa in Western blot analysis. The sensitivity, specificity and similarity of the latex agglutination test, in comparison to ELISA, were 87.94, 90.29 and 88.93 %, respectively. The developed latex agglutination test resulted in a positive reaction at the presence of a minimum antibody concentration equal to 308.63 μg/mL. The results indicate that the latex agglutination test is effective for the rapid diagnosis and control of Ornithobacterium infection in turkeys.